2014
DOI: 10.1111/joop.12094
|View full text |Cite
|
Sign up to set email alerts
|

Challenge versus hindrance job demands and well‐being: A diary study on the moderating role of job resources

Abstract: The present study among 158 primary school teachers in Croatia integrated the challenge‐hindrance stressor framework in job demands–resources (JD–R) theory. We hypothesized that hindrance job demands would be negatively related to well‐being and that job resources could buffer this relationship. In addition, we hypothesized that challenge job demands would be positively related to well‐being and that job resources would boost this relationship. The study employed a quantitative daily diary methodology. Teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
220
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(262 citation statements)
references
References 74 publications
17
220
0
4
Order By: Relevance
“…That is, when people are confronted with challenges, resources become particularly salient and increase the motivating power of the challenges. This was confirmed in their empirical study (Tadić et al, 2014).…”
Section: Moderating Role Of Transition Resourcessupporting
confidence: 68%
See 2 more Smart Citations
“…That is, when people are confronted with challenges, resources become particularly salient and increase the motivating power of the challenges. This was confirmed in their empirical study (Tadić et al, 2014).…”
Section: Moderating Role Of Transition Resourcessupporting
confidence: 68%
“…It is then believed that resources enable employees to cope better with the job demands and, thus, that they can buffer their negative impact. In line with this reasoning, a few studies have indeed found resources to lower the demotivating impact of, among others, emotional and physical demands Hakanen, Bakker, & Demerouti, 2005;Tadić et al, 2014). However, this buffering impact has not always been found, an observation that stimulated Tadić and colleagues (2014) to argue that resources could have a boosting-rather than a buffering-impact on challenging demands.…”
Section: Moderating Role Of Transition Resourcesmentioning
confidence: 79%
See 1 more Smart Citation
“…However, in terms of challenging job demands, research has shown that stimulating and challenging job tasks impact employee motivation positively (Crawford, LePine & Rich, 2010;LePine, Podsakoff & LePine, 2005), whereas hindering job demands have been shown to be related to employee exhaustion and cynicism (LePine et al, 2005;Van den Broeck, De Cuyper, De Witte & Vansteenkiste, 2010). Hindering job demands contribute to the eroding of energy and health impairment that leads to burnout and eventually being unwell (Tadic, Bakker & Oerlemans, 2015). Job crafters therefore address their job demands and job resources in a variety of constructive ways, like seeking resources (e.g., more autonomy on certain tasks, asking supervisors for more feedback regarding their performance), seeking challenges (e.g., challenging job demands to increase their mastery and personal growth), and reducing demands (e.g., hindering demands such as role conflict) (cf.…”
Section: Deconstructing Job Craftingmentioning
confidence: 99%
“…Finally, in a recent daily diary study, Tadic et al (2015) investigated the role of job resources in the context of the challenge-hindrance stressor framework (Cavanaugh et al 2000), focusing on two well-being indicators that are closely related to workrelated flow, namely daily positive affect and daily work engagement. Teachers were asked to fill out a daily diary questionnaire for several days in a row.…”
Section: Antecedents Of Work-related Flowmentioning
confidence: 99%